An Analysis of the Potential Ramifications of People for the Ethical Treatment of Property Owners v. United States Fish and Wildlife Service (PETPO v. FWS). Issue 1 (2nd January 2017) - Scanlon, Dennis
ABSTRACT: In 2013 a lawsuit was filed against the U.S. Fish and Wildlife Service, contesting the constitutionality of the government's ability to regulate the Utah prairie dog on private land under the Endangered Species Act of 1973. There, the court held that constraints enforced under the ESA on the "taking" of the Utah prairie dog were unconstitutional, primarily because the species is found exclusively in Utah and the regulations thus exceed the government's power under the commerce clause. Here, an analysis of this unprecedented ruling was conducted to investigate its potential long-term implications. Ultimately, this case is expected to have lasting impacts on the future of endangered and threatened species conservation under the ESA.